2007
DOI: 10.1080/10641960601096760
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Relationship of Nocturnal Blood Pressure Variability with Coronary Artery Disease in Diabetic Nephropathy

Abstract: Evidence suggests a relationship between short-term blood pressure (BP) variability and cardiovascular target-organ damage. Although a blunted nocturnal decrease in BP and reduced heart rate variability have been shown to be associated with cardiovascular morbidity in diabetic patients, little information is available on short-term BP variability. In this study, short-term BP variability was assessed in 36 subjects with type 2 diabetes and overt nephropathy who underwent ambulatory BP monitoring, and the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Several previous studies have reported that short-term BP variability estimated by noninvasive ambulatory BP monitoring is associated with cardiovascular disease in hypertensive patients. [8][9][10] The results of our previous cross-sectional study also showed that short-term BP variability was significantly increased in overt diabetic nephropathy patients with coronary artery disease, 26 and in particular, an increase in nighttime short-term BP variability was associated with the plasma concentration of noradrenaline, as well as with the prevalence of coronary artery disease in these diabetic nephropathy patients. 26 There is a well-established role for the renin-angiotensin system in promoting hypertension-and diabetes-related organ damage, including atherosclerosis and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Several previous studies have reported that short-term BP variability estimated by noninvasive ambulatory BP monitoring is associated with cardiovascular disease in hypertensive patients. [8][9][10] The results of our previous cross-sectional study also showed that short-term BP variability was significantly increased in overt diabetic nephropathy patients with coronary artery disease, 26 and in particular, an increase in nighttime short-term BP variability was associated with the plasma concentration of noradrenaline, as well as with the prevalence of coronary artery disease in these diabetic nephropathy patients. 26 There is a well-established role for the renin-angiotensin system in promoting hypertension-and diabetes-related organ damage, including atherosclerosis and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 69%
“…of all HR values at 30-min intervals divided by mean HR. 8,9,26 Electrocardiogram and power spectral analysis of R-R intervals…”
Section: Determination Of 24-h Bp and Short-term Bp Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, previous human studies have also shown increases in ambulatory BP variability to be related to atherosclerosis, urinary protein excretion and cardiovascular disease in Japanese patients with type 2 diabetes. [21][22][23] It was postulated that the presence of advanced atherosclerosis and impaired baroreflex sensitivity, which was associated with diabetic neuropathy, could lead to increased variability in BP in diabetic patients.…”
Section: Coefficient Variation Of Home Blood Pressure E Ushigome Et Almentioning
confidence: 99%
“…5,6 Short-term BP variability has also been suggested to be clinically relevant because hypertensive patients with similar mean 24 h BP values exhibit more severe organ damage when their short-term BP variability is greater. [7][8][9][10][11][12][13][14] With respect to home-measured BP, several clinical studies (both long-term followup surveys and cross-sectional studies) have provided an epidemiological basis for supporting the greater accuracy of home BP monitoring than clinic BP measurement for the prognosis of fatal and nonfatal cardiovascular disease (CVD). There is a general consensus that home BP monitoring is more convenient, more readily available and less costly than ambulatory BP monitoring, but ambulatory BP monitoring has been recognized to be superior for certain clinical problems, for example, for the detection of non-dippers or sleep BP in patients with chronic renal disease, autonomic neuropathies or sleep apnea, and for the estimation of short-term BP variability.…”
Section: T He Accumulated Results Of Clinical Trialsmentioning
confidence: 99%